Systematic Appraisal of the Impacts of Transformational Leadership on Innovation Behaviour Among Nurses - Ibrahim Saleh Almahayawy, (British Journal of Healthcare and Medical Research, 2023)
Background: The healthcare industry is among the most essential in any economy. The challenges that confront the sector are wide and far-reaching. Given the economic challenges that are unpredictable and difficult to plan for, the healthcare sector is facing a host of challenges. This study aims to explore the important role of transformational leadership that can inspire innovative work behaviour of nurses to perform their tasks most efficiently. Method: the initial online database search for relevant literature yielded 4160 papers from two databases. After excluding duplicates and those for which full texts were not available, and other exclusion criteria, six papers were selected for extraction of results. First, rating of the quality of these papers was done adapting the CASP model for one qualitative review and Axis analysis for five papers. In depth analysis of six papers was further done are results presented for discussions. Results: A few critical issues emerged which were considered in the discussions of these findings. Considered along with works reviewed in the Review of Literature chapter, the outcome of the work led to some useful conclusions that there is a correlation between transformational leadership and innovative work behaviour among nurses. There is sufficient evidence from the six papers analysed on a positive relationship between transformational leadership and nurse innovation behaviour amid certain mediating factors. Conclusion: More nurse innovative approaches need to be directly applied to achieve the triple aim of care quality, service, and affordability across all health care organisations in the ever-changing scenarios of evidence-based medical practices.